Solid-state electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202311063000.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-08-22
AI Technical Summary
[0006]本发明的主要目的在于提供一种固态电解质及其制备方法和应用,以解决现有技术中固态电解质制备过程中存在硫化锂原料溶解困难或制备成本高或固态电解质纯度低的问题
[0018]应用本发明的技术方案制备得到的固态电解质相比于常规方法制备的固态电解质,其纯度更高,硫化锂杂质含量明显降低,离子电导率大幅度提升,应用于锂离子电池中,表现出更优的倍率性能和循环性能。
Smart Images

Figure CN116995306B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion batteries, and more specifically, to a solid electrolyte, its preparation method, and its application. Background Technology
[0002] Solid-state lithium batteries, which utilize sulfide solid electrolytes, offer higher energy density and better safety compared to liquid lithium-ion batteries, making them highly promising for market adoption. However, the chemical instability, difficulty in production and storage, and high cost of lithium sulfide, the precursor to sulfide solid electrolytes, severely hinder their commercialization.
[0003] Currently, the synthesis methods of sulfide solid electrolytes can be divided into two main categories: solid-phase ball milling and liquid-phase methods. Solid-phase ball milling involves directly ball milling lithium sulfide and other raw materials in a ball mill. The rotation and collision between the milling jar and the milling beads induce a full reaction between the raw materials through mechanical stress, thereby obtaining the sulfide solid electrolyte. Invention patent CN113839086A discloses a method for preparing a sulfide solid electrolyte. The specific preparation steps are as follows: First, metallic lithium, elemental sulfur, phosphorus pentasulfide, and lithium halide are ball-milled to obtain a solid mixture of the above substances. Then, the mixture is sintered in a solid state at a certain temperature to obtain Li6PS5X powder. Finally, the powder is further crushed to control the particle size of the Li6PS5X product. The final sulfide solid electrolyte mainly consists of Li6PS5Cl and also contains a small amount of lithium sulfide impurities. Because this solid-phase ball milling method relies solely on mechanical stress to fully react the electrolyte precursors, the preparation process is time-consuming and energy-intensive. Moreover, the sulfide electrolyte prepared by this method is prone to contamination by impurities from the grinding beads and the grinding jar wall, resulting in poor product reproducibility and hindering large-scale industrialization.
[0004] The liquid-phase method for preparing solid electrolytes involves preparing raw materials into solutions or suspensions, and then allowing the reactions between the raw materials to occur in the liquid phase. Invention patent CN115101807A discloses a method for preparing solid electrolytes, with the following specific steps: First, lithium sulfide and phosphorus pentasulfide react to generate a Li3PS4·3THF complex, which is then added to tetrahydrofuran to obtain a Li3PS4·3THF / THF suspension. Subsequently, a lithium sulfide-lithium halide solution is directly added to the prepared Li3PS4·3THF / THF suspension. After sufficient reaction, the supernatant is collected by centrifugation and vacuum dried to obtain Li6PS5Cl powder. Further, the powder is pre-heat-treated under anhydrous and oxygen-free conditions and then ball-milled at low temperature in a stirred ball mill to obtain a powdered sulfide solid electrolyte. Although this method is easily scalable and suitable for large-scale industrial production, the solid electrolyte prepared by this method still contains a small amount of lithium sulfide impurities. In addition, how to fully dissolve the precursor raw materials in the solution to form a solution is currently a key research focus.
[0005] Therefore, both solid-phase ball milling and liquid-phase methods for preparing sulfide solid electrolytes require lithium sulfide as a raw material. However, lithium sulfide is extremely unstable in air, readily hydrolyzing to form lithium hydroxide and releasing toxic hydrogen sulfide gas. Furthermore, lithium sulfide cannot form stable hydrates (such as Na₂S·9H₂O) like other alkali metal sulfides, making its preparation and storage difficult. On the other hand, the low abundance of lithium in the Earth's crust makes lithium-containing compounds more expensive than other alkali metal compounds in the same group. In summary, the difficulty in preparing and storing lithium sulfide, along with its high price, hinders the application and further commercialization of sulfide solid electrolytes. Therefore, it is necessary to develop a new method for preparing sulfide solid electrolytes to address the problems of high preparation costs, difficulty in dissolving lithium sulfide raw materials, and low purity of solid electrolytes in existing technologies. Summary of the Invention
[0006] The main objective of this invention is to provide a solid electrolyte, its preparation method, and its application, in order to solve the problems of difficulty in dissolving lithium sulfide raw materials, high preparation costs, or low purity of solid electrolytes in the preparation process of existing solid electrolytes.
[0007] To achieve the above objectives, according to one aspect of the present invention, a method for preparing a solid electrolyte is provided, the method comprising the following steps: step S1, taking lithium metal, hydrogen sulfide gas and solvent to perform a chemical reaction to obtain a lithium sulfide solution; step S2, adding a precursor to the lithium sulfide solution for heat treatment to obtain a solid electrolyte; wherein the solvent is a C1 to C5 alcohol solvent.
[0008] Further, in step S2, the precursor is selected from one or more of lithium chloride, phosphorus pentasulfide, tin disulfide, or germanium disulfide; the amount of precursor added is 0.01 to 30 wt% of the total weight of the lithium sulfide solution; the solvent is selected from C1 to C5 monohydric alcohols and / or polyhydric alcohols; preferably, the solvent is selected from one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, ethylene glycol, glycerol, or butanediol.
[0009] Further, in step S2, the heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the first heat treatment is carried out in a vacuum heating and drying device, preferably selected from one or more of a vacuum drying oven, a rotary evaporator or a vacuum atmosphere furnace; more preferably, the temperature of the first heat treatment is 40 to 200°C, the treatment time is 1 to 72 hours, and the vacuum degree is -0.1 to 0 MPa.
[0010] Furthermore, the second heat treatment is carried out in one or more of an atmosphere furnace, muffle furnace, tube furnace or vacuum drying oven. More preferably, the second heat treatment is to raise the temperature from the first heat treatment temperature to 120-700°C at a heating rate of 1-10°C / min and for a treatment time of 1-20h.
[0011] Further, in step S1, the form of metallic lithium is selected from one or more of lithium foil, lithium wire, lithium strip, lithium powder, lithium block, lithium briquettes or lithium rods; preferably, the amount of metallic lithium is 0.01 to 10 wt% of the solvent weight.
[0012] Furthermore, both steps S1 and S2 are performed in an inert atmosphere; the gas in the inert atmosphere in step S1 is selected from one or more of argon, helium, neon, krypton or xenon; the gas in the inert atmosphere in step S2 is selected from one or more of nitrogen, argon, helium, neon, krypton or xenon.
[0013] Furthermore, in step S1, the chemical reaction is carried out under stirring conditions, with a stirring speed of 200-1000 rpm and a stirring time of 1-24 h; preferably, the reaction temperature of the chemical reaction is 0-78℃ and the reaction time is 0.5-24 h.
[0014] Furthermore, in step S1, the flow rate of hydrogen sulfide gas is 1–10000 mL / min, and the introduction time of hydrogen sulfide gas is 0.01–100 h.
[0015] Furthermore, in step S2, the lithium sulfide solution needs to be stirred before heat treatment; preferably, the stirring speed is 200-1000 rpm and the stirring time is 0.5-72 h.
[0016] According to another aspect of the present invention, a solid electrolyte is provided, which is a solid electrolyte obtained by the above-described method for preparing a solid electrolyte.
[0017] According to another aspect of the present invention, a lithium-ion battery is provided, which includes the above-described solid electrolyte, or a solid electrolyte obtained by the above-described method for preparing solid electrolyte.
[0018] The solid electrolyte prepared using the technical solution of this invention has higher purity, significantly lower lithium sulfide impurity content, and greatly improved ionic conductivity compared to solid electrolytes prepared by conventional methods. When applied to lithium-ion batteries, it exhibits superior rate performance and cycle performance. Attached Figure Description
[0019] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0020] Figure 1 The XRD pattern of the solid electrolyte obtained in Example 1 of this application is shown. Detailed Implementation
[0021] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0022] As described in the background section of this invention, existing technologies for preparing solid electrolytes suffer from problems such as difficulty in dissolving lithium sulfide raw materials, high preparation costs, or low purity of the solid electrolyte. This invention provides a method for preparing a solid electrolyte, comprising the following steps: Step S1, reacting metallic lithium, hydrogen sulfide gas, and a solvent to obtain a lithium sulfide solution; Step S2, adding a precursor to the lithium sulfide solution and performing heat treatment to obtain a solid electrolyte; wherein the solvent is a C1-C5 alcohol solvent. The reaction equation for preparing the solid electrolyte is shown below.
[0023] The reaction equations for the synthesis of lithium sulfide are: 2ROH + 2Li = 2ROLi + H2; 2ROLi + H2S = Li2S + 2ROH; the overall equation for the synthesis of lithium sulfide is: 2Li + H2S = Li2S + H2. Where R refers to a C1-C5 alkyl group.
[0024] The general reaction formula for synthesizing solid electrolytes is: Li2S + XS → LiXS (the product is a solid electrolyte of binary sulfide, where X is P, Ge or Sn) or Li2S + P2S5 + XS (or LiX) → LiPXS (the product is a solid electrolyte of ternary sulfide, where X is Cl, Ge or Sn).
[0025] In existing liquid-phase methods for preparing solid-state electrolytes, lithium sulfide is chemically reactive and unstable, easily absorbing water vapor and hydrolyzing. Furthermore, the purity of purchased lithium sulfide is insufficient, containing small amounts of impurities, making it difficult to dissolve in organic solvents when used as a reaction raw material (solid particulate form) for solid-state electrolyte preparation. This invention first synthesizes lithium sulfide raw material, then creatively uses the homogeneous and stable lithium sulfide solution obtained from the synthesis as the reaction solution for preparing the solid-state electrolyte. In particular, this invention selects C1-C5 alcohol solvents. Lithium sulfide prepared in this solvent exhibits better solubility and no side reactions compared to the mixed organic solvents (e.g., ethanol / tetrahydrofuran mixtures) used in existing technologies to dissolve lithium sulfide. It is also more affordable, reducing production costs and making it suitable for large-scale production with promising industrialization prospects. In summary, the solid-state electrolyte preparation method of this invention effectively solves the problem of poor solubility of lithium sulfide raw material in liquid solvents in existing technologies, while also saving the cost of purchasing expensive lithium sulfide raw materials. Secondly, the preparation method of this invention avoids the ball milling process used in the liquid-phase method of existing technologies to increase the solubility of raw materials, thereby preventing impurities from the milling beads and the walls of the milling tank from mixing into the electrolyte, improving the purity of the solid electrolyte, and thus improving its electrochemical performance. Thirdly, in the preparation of lithium sulfide solution in this invention, hydrogen sulfide gas is used as a raw material. This gas is an industrial waste gas, and the consumption of hydrogen sulfide gas generates hydrogen gas with high added value (see the reaction equation for the synthesis of lithium sulfide for details), thus meeting the requirements of green chemistry, having higher economic benefits and commercial potential, and broad application prospects.
[0026] In a preferred embodiment, in step S2, the precursor is selected from one or more of lithium chloride, phosphorus pentasulfide, tin disulfide, or germanium disulfide. The solid electrolyte prepared using the above precursor as raw material has high stability and safety performance, and the solid electrolyte has high ionic conductivity during application, exhibiting excellent electrochemical performance. More preferably, the amount of precursor added accounts for 0.01 to 30 wt% of the total weight of the lithium sulfide solution.
[0027] To further improve the synthesis rate of lithium sulfide and promote the full progress of the chemical reaction, the solvent is preferably selected from C1-C5 monohydric alcohols and / or polyhydric alcohols. More preferably, the solvent is selected from one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, ethylene glycol, glycerol, or butanediol, so that lithium sulfide has better solubility in the solvent and the resulting lithium sulfide solution has better stability and is more homogeneous.
[0028] In a preferred embodiment, when the precursor is lithium chloride, the lithium chloride includes anhydrous lithium chloride or hydrated lithium chloride. The hydrated lithium chloride needs to undergo dehydration treatment, which involves heating the hydrated lithium chloride using a heating and drying device. The heating and drying device is selected from one or more of a tube furnace, muffle furnace, or vacuum drying oven. The heating temperature is 60–250°C, the vacuum degree is -0.1–0 MPa, and the treatment time is 2–120 h. To ensure more thorough dehydration, a further preferred heating temperature is 160–200°C, the vacuum degree is -0.1–-0.08 MPa, and the treatment time is 72–96 h.
[0029] In a preferred embodiment, in step S2 of preparing the solid electrolyte material, in order to make the solid electrolyte have higher purity and better electrochemical performance, the heat treatment preferably includes performing a first heat treatment and a second heat treatment in sequence. Preferably, the first heat treatment is performed in a vacuum heating and drying device. More preferably, the vacuum heating and drying device is selected from one or more of a vacuum drying oven, a rotary evaporator, or a vacuum atmosphere furnace. More preferably, the temperature of the first heat treatment is 40 to 200°C, the treatment time is 1 to 72 hours, and the vacuum degree is -0.1 to 0 MPa, so that the solvent can be completely evaporated, thereby avoiding the influence of solvent residue on the purity of the solid electrolyte and improving the electrochemical performance of the solid electrolyte.
[0030] To further improve the purity of the solid electrolyte, a second heat treatment is performed on the solid electrolyte material. Preferably, the second heat treatment is carried out in one or more of the following equipment: atmosphere furnace, muffle furnace, tube furnace, or vacuum drying oven. More preferably, the second heat treatment involves heating from the first heat treatment temperature to 120–700°C at a heating rate of 1–10°C / min for a treatment time of 1–20 h. This further reduces the influence of other impurities in the solid electrolyte on the electrolyte purity, thereby improving the purity and conductivity of the solid electrolyte.
[0031] To further improve the conductivity of the solid electrolyte, in step S1, the amount of metallic lithium preferably accounts for 0.01 to 10 wt% of the solvent weight, so that the chemical reaction for preparing lithium sulfide can be fully carried out. Preferably, the form of metallic lithium is selected from one or more of lithium foil, lithium wire, lithium strip, lithium powder, lithium block, lithium butyl or lithium rod.
[0032] In a preferred embodiment, considering that the chemical properties of inert gases are inert and relatively stable, in order to prevent the reactants from reacting with components in the air at high temperatures during the preparation of solid electrolytes, it is preferred that steps S1 and S2 are both carried out under an inert atmosphere. In order to further avoid the reaction between nitrogen and lithium metal, it is preferred that the gas in the inert atmosphere in step S1 is selected from one or more of argon, helium, neon, krypton or xenon. More preferably, the gas in the inert atmosphere in step S2 is selected from one or more of nitrogen, argon, helium, neon, krypton or xenon.
[0033] In a preferred embodiment, in order to further promote the full reaction of the chemical reaction, the chemical reaction is carried out under stirring conditions, with a stirring speed of 200 to 1000 rpm and a stirring time of 1 to 24 h, and the reaction temperature of the chemical reaction is 0 to 78 °C and the reaction time is 0.5 to 24 h.
[0034] In a preferred embodiment, in step S1, the flow rate of hydrogen sulfide gas is preferably 1-10000 mL / min, and the introduction time of hydrogen sulfide gas is 0.01-100 h, which can further promote the formation of lithium sulfide products. The hydrogen sulfide gas is derived from industrial waste gas. Using it as a raw material to prepare lithium sulfide meets the requirements of green chemistry, consumes industrial waste gas to produce hydrogen gas with high added value, and thus shows high economic benefits and broad application prospects.
[0035] In a preferred embodiment, to further promote the smooth progress of the lithium sulfide reaction, the hydrogen sulfide gas in step S1 is preferably selected from a hydrogen sulfide-inert gas mixture, wherein the inert gas is selected from one or more of argon, helium, neon, krypton or xenon, and more preferably the volume ratio of the inert gas to the hydrogen sulfide gas is (0.1 to 9):1.
[0036] To further improve the electrochemical and safety performance of the solid electrolyte, as well as its purity, in step S2 of the preparation process, the lithium sulfide solution needs to be stirred before heat treatment. The stirring speed is preferably 200-1000 rpm and the stirring time is 0.5-72 h, so that the chemical reaction for preparing the solid electrolyte can proceed smoothly and the purity and electrochemical performance of the solid electrolyte can be improved.
[0037] Another aspect of the present invention provides a solid electrolyte obtained by the above-described method for preparing solid electrolytes. This solid electrolyte exhibits high ionic conductivity and high purity, demonstrating excellent electrochemical performance.
[0038] Another aspect of the present invention provides a lithium-ion battery comprising the above-described solid electrolyte material, or a solid electrolyte material obtained by the above-described method for preparing the solid electrolyte material. This lithium-ion battery exhibits high conductivity and better electrochemical performance and stability.
[0039] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.
[0040] Example 1
[0041] Step S1: In an argon-atmospheric glove box, first take 64.66 mg of lithium metal block and add it to 20 mL of anhydrous ethanol. Pass hydrogen sulfide gas through it at a flow rate of 50 sccm for 2 min 19 s. Stir at 25 °C and 400 rpm for 1 h to obtain a lithium sulfide solution.
[0042] Step S2: In an argon-atmospheric glove box, 78.98 mg of lithium chloride and 207.03 mg of phosphorus pentasulfide were added to the aforementioned lithium sulfide solution as precursors. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing a solid electrolyte. The solution was then dried under vacuum at 140°C in a vacuum oven. The vacuum degree was -0.095 MPa, and the processing time was 24 hours. After removing the solvent, a coarse powder containing the solid electrolyte was obtained. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of the solid electrolyte material Li6PS5Cl. The X-ray diffraction (XRD) pattern of this solid electrolyte is shown in the attached figure. Figure 1 As shown.
[0043] Example 2
[0044] Step S1: In an argon-atmosphere glove box, first take 115.66 mg of lithium metal and add it to 100 mL of anhydrous isopropanol. Pass a mixture of 80% argon and 20% hydrogen sulfide (volume ratio) through it at a flow rate of 100 sccm for 21 min 42 s. Stir at 40 °C and 600 rpm for 1 h to obtain a lithium sulfide solution.
[0045] In step S2, 1234.44 mg of phosphorus pentasulfide was taken as a precursor and added to the above lithium sulfide solution in an argon-atmospheric glove box. The mixture was stirred at 40°C and 600 rpm for 24 h to obtain a solution containing solid electrolyte. Then, the solution was dried under vacuum at 120°C in a rotary evaporator with a vacuum degree of -0.08 MPa for 36 h to remove the solvent, resulting in a coarse powder containing solid electrolyte. This powder was then placed in a tube furnace and heated at 300°C for 5 h at a heating rate of 5°C / min to obtain 2 g of solid electrolyte material Li3PS4.
[0046] Example 3
[0047] Step S1: In an argon-atmospheric glove box, first take 546.70 mg of lithium metal block and add it to 100 mL of anhydrous ethanol. Pass hydrogen sulfide gas through it at a flow rate of 100 sccm for 19 min 32 s. Stir at 25 °C and 400 rpm for 1 h to obtain a lithium sulfide solution.
[0048] Step S2: In an argon-atmospheric glove box, 1440.00 mg of tin disulfide and 1750.60 mg of phosphorus pentasulfide were added as precursors to the aforementioned lithium sulfide solution. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing solid electrolyte. Then, the solution was vacuum-dried at 200°C in a vacuum furnace. The vacuum degree was -0.098 MPa, and the processing time was 48 hours. After removing the solvent, a coarse powder containing solid electrolyte was obtained. This powder was then placed in the furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 5 g of solid electrolyte material Li. 10 SnP2S 12 .
[0049] Example 4
[0050] Step S1: In an argon-atmospheric glove box, first take 64.66 mg of lithium metal block and add it to 20 mL of anhydrous ethanol. Pass hydrogen sulfide gas through it at a flow rate of 50 sccm for 2 min 19 s. Stir at 25 °C and 400 rpm for 1 h to obtain a lithium sulfide solution.
[0051] In step S2, 78.98 mg of lithium chloride and 207.03 mg of phosphorus pentasulfide were added to the lithium sulfide solution in an argon-atmospheric glove box as precursors. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing solid electrolyte. The lithium chloride used in this step was hydrated lithium chloride, which was dried by heating. The dehydration conditions were heating at 180°C for 72 hours in a vacuum oven with a vacuum degree of -0.095 MPa. Then, the solution was vacuum-dried at 140°C in a vacuum oven with a vacuum degree of -0.095 MPa for 24 hours to remove the solvent, resulting in a coarse powder containing solid electrolyte. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of solid electrolyte material Li6PS5Cl.
[0052] Example 5
[0053] Step S1: In an argon-atmospheric glove box, first take 64.66 mg of lithium metal block and add it to 20 mL of anhydrous methanol. Pass hydrogen sulfide gas through it at a flow rate of 50 sccm for 2 min 19 s. Stir at 25 °C and 400 rpm for 1 h to obtain a lithium sulfide solution.
[0054] In step S2, 78.98 mg of lithium chloride and 207.03 mg of phosphorus pentasulfide were added to the lithium sulfide solution in an argon-atmospheric glove box as precursors. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing solid electrolyte. The solution was then dried under vacuum at 140°C in a vacuum oven. The vacuum level was -0.095 MPa, and the treatment time was 24 hours. After removing the solvent, a coarse powder containing solid electrolyte was obtained. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of solid electrolyte material Li6PS5Cl.
[0055] Example 6
[0056] Step S1: In an argon-atmospheric glove box, first take 64.66 mg of lithium metal and add it to 40 mL of anhydrous ethylene glycol. Pass hydrogen sulfide gas through it at a flow rate of 50 sccm for 2 min 19 s. Stir at 25 °C and 400 rpm for 1 h to obtain a lithium sulfide solution.
[0057] In step S2, 78.98 mg of lithium chloride and 207.03 mg of phosphorus pentasulfide were added to the lithium sulfide solution in an argon-atmospheric glove box as precursors. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing solid electrolyte. The solution was then dried under vacuum at 140°C in a vacuum oven. The vacuum level was -0.095 MPa, and the treatment time was 24 hours. After removing the solvent, a coarse powder containing solid electrolyte was obtained. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of solid electrolyte material Li6PS5Cl.
[0058] Example 7
[0059] Step S1: In an argon-atmospheric glove box, first take 64.66 mg of lithium metal block and add it to 50 mL of anhydrous glycerol. Pass hydrogen sulfide gas through it at a flow rate of 50 sccm for 2 min 19 s. Stir at 25 °C and 400 rpm for 1 h to obtain a lithium sulfide solution.
[0060] In step S2, 78.98 mg of lithium chloride and 207.03 mg of phosphorus pentasulfide were added to the lithium sulfide solution in an argon-atmospheric glove box as precursors. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing solid electrolyte. The solution was then dried under vacuum at 140°C in a vacuum oven. The vacuum level was -0.095 MPa, and the treatment time was 24 hours. After removing the solvent, a coarse powder containing solid electrolyte was obtained. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of solid electrolyte material Li6PS5Cl.
[0061] Comparative Example 1
[0062] In an argon-atmospheric glove box, 128.42 mg of lithium sulfide and 207.04 mg of phosphorus pentasulfide were first added to 20 mL of tetrahydrofuran and stirred at 25 °C and 400 rpm for 24 h to obtain a Li3PS4·3THF / tetrahydrofuran suspension. Simultaneously, 85.62 mg of lithium sulfide and 78.97 mg of lithium chloride were added to 20 mL of ethanol solution and stirred at 25 °C and 400 rpm for 24 h to obtain a lithium sulfide-lithium chloride / ethanol solution. The two solutions were then mixed and stirred at 25 °C and 400 rpm for 24 h to obtain a solution containing a solid electrolyte. Then, the above solution was dried in a vacuum oven at 140°C with a vacuum degree of -0.095 MPa for 24 hours to remove the solvent and obtain coarse powder containing solid electrolyte. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of solid electrolyte material Li6PS5Cl.
[0063] Comparative Example 2
[0064] Step S1: In an argon-atmospheric glove box, first take 64.66 mg of lithium metal and add it to 20 mL of tetrahydrofuran. Pass hydrogen sulfide gas through it at a flow rate of 50 sccm for 2 min 19 s. Stir at 25 °C and 400 rpm for 1 h to obtain a suspension.
[0065] In step S2, 78.98 mg of lithium chloride and 207.03 mg of phosphorus pentasulfide were added to the lithium sulfide solution in an argon-atmospheric glove box as precursors. The mixture was stirred at 25°C and 400 rpm for 24 hours to obtain a solution containing solid electrolyte. The solution was then dried under vacuum at 140°C in a vacuum oven. The vacuum level was -0.095 MPa, and the treatment time was 24 hours. After removing the solvent, a coarse powder containing solid electrolyte was obtained. This powder was then placed in a muffle furnace and heated at 550°C for 10 hours at a heating rate of 5°C / min to obtain 0.5 g of solid electrolyte material Li6PS5Cl.
[0066] Performance testing:
[0067] (1) Conductivity:
[0068] 120 mg of solid electrolyte powder was placed in a cylindrical mold (φ = 10 mm). Two stainless steel pillars with the same inner diameter were inserted into both ends of the electrolyte powder. The pressure was increased to 200 MPa and held for 5 minutes using a hydraulic press. After the pressure holding period, the ionic conductivity was measured at room temperature with a bias voltage of 10 mV. The electrochemical workstation model was CHI-760e (manufactured by Shanghai Chenhua Scientific Instruments Co., Ltd.), and the frequency range was 0.1–107 Hz. After the test, the electrolyte sheet was removed, and the thickness of the electrolyte sheet was measured using a micrometer. The ionic conductivity of the powder was calculated using the formula: ionic conductivity = d / AR, where d is the thickness of the electrolyte layer, A is the area of the electrolyte layer, and R is the impedance value.
[0069] (2) Purity / Impurity content:
[0070] After XRD testing, the impurity content was calculated using Rietveld refinement software. The refinement calculation software was Fullproof. The XRD testing range was 5–90°, the scan rate was 1° / min, and the XRD wavelength was [missing value]. (Cu-Kα).
[0071] The solid electrolytes prepared in the above examples and comparative examples were tested, and the results are shown in Table 1 below:
[0072] Table 1
[0073] Example 1 120 50.3 3.0 Example 2 200 5.4 2.8 Example 3 180 32.5 2.0 Example 4 140 46.3 2.5 Example 5 200 30.8 3.5 Example 6 400 20.6 4.5 Example 7 320 22.4 5.2 Comparative Example 1 800 10.5 15.2 Comparative Example 2 1000 0.75 32.0
[0074] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0075] The test data from Examples 1, 5, 6, 7 and Comparative Example 2 show that when the solid electrolyte preparation method of the present invention is used, and the solvent is a C1-C5 alcohol solvent (e.g., anhydrous ethanol in Example 1, anhydrous methanol in Example 5, anhydrous ethylene glycol in Example 6, or anhydrous glycerol in Example 7), the prepared solid electrolyte has high ionic conductivity, high purity, and low lithium sulfide impurity content. However, when tetrahydrofuran (Comparative Example 2) is used as the solvent, its poor solubility for lithium sulfide results in low purity of the obtained solid electrolyte, high lithium sulfide content, and poor ionic conductivity.
[0076] The test data from Examples 2 and 3 show that when Li3PS4 and Li are prepared using the solid electrolyte preparation method of the present invention, respectively... 10 SnP2S 12 Compared with conventional preparation methods, solid electrolytes have higher ionic conductivity and higher purity.
[0077] The test data from Examples 1 and 4 and Comparative Example 1 show that, compared with solid electrolytes prepared by conventional methods, the solid electrolyte preparation method of the present invention produces a uniform and stable lithium sulfide solution, which effectively solves the problem of poor solubility of lithium sulfide raw materials in liquid solvents in the prior art. This results in a significant increase in the ionic conductivity of the solid electrolyte, as well as higher purity and lower impurity content.
[0078] In summary, the solid electrolyte prepared using the present invention has higher purity, significantly lower lithium sulfide impurity content, and significantly improved ionic conductivity compared to solid electrolytes prepared by conventional methods. When applied to lithium-ion batteries, it exhibits superior rate performance and cycle performance. The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a solid electrolyte, characterized in that, The preparation method includes the following steps: Step S1: Take lithium metal, hydrogen sulfide gas and solvent and carry out a chemical reaction to obtain lithium sulfide solution; Step S2: The precursor is added to the lithium sulfide solution for heat treatment to obtain the solid electrolyte; Wherein, the solvent is a C1-C5 alcohol solvent; the precursor is selected from one or more of lithium chloride, phosphorus pentasulfide, tin disulfide or germanium disulfide; both steps S1 and S2 are carried out under an inert atmosphere.
2. The preparation method according to claim 1, characterized in that, The amount of the precursor added is 0.01 to 30 wt% of the total weight of the lithium sulfide solution.
3. The preparation method according to claim 1, characterized in that, The solvent is selected from C1 to C5 monohydric alcohols and / or polyhydric alcohols.
4. The preparation method according to claim 3, characterized in that, The solvent is selected from one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, ethylene glycol, glycerol, or butanediol.
5. The preparation method according to claims 1 to 4, characterized in that, In step S2, the heat treatment includes a first heat treatment and a second heat treatment performed sequentially.
6. The preparation method according to claim 5, characterized in that, The first heat treatment is carried out in a vacuum heating and drying equipment.
7. The preparation method according to claim 6, characterized in that, The vacuum heating and drying equipment is selected from one or more of the following: vacuum drying oven, rotary evaporator, or vacuum atmosphere furnace.
8. The preparation method according to claim 5, characterized in that, The first heat treatment temperature is 40~200℃, the treatment time is 1~72h, and the vacuum degree is -0.1~0MPa.
9. The preparation method according to claim 5, characterized in that, The second heat treatment is carried out in one or more of an atmosphere furnace, muffle furnace, tube furnace or vacuum drying oven.
10. The preparation method according to claim 9, characterized in that, The second heat treatment involves raising the temperature from the first heat treatment temperature to 120~700℃, with a heating rate of 1~10℃ / min and a treatment time of 1~20h.
11. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1, the form of the metallic lithium is selected from one or more of lithium foil, lithium wire, lithium strip, lithium powder, lithium block, lithium dies, or lithium rods.
12. The preparation method according to claim 11, characterized in that, The amount of lithium metal used is 0.01 to 10 wt% of the solvent weight.
13. The preparation method according to any one of claims 1 to 4, characterized in that, The gas in the inert atmosphere in step S1 is selected from one or more of argon, helium, neon, krypton, or xenon.
14. The preparation method according to any one of claims 1 to 4, characterized in that, The gas in the inert atmosphere in step S2 is selected from one or more of nitrogen, argon, helium, neon, krypton, or xenon.
15. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1, the chemical reaction is carried out under stirring conditions, the stirring speed is 200~1000 rpm, and the stirring time is 1~24h.
16. The preparation method according to any one of claims 1 to 4, characterized in that, The reaction temperature of the chemical reaction is 0~78℃, and the reaction time is 0.5~24h.
17. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1, the flow rate of the hydrogen sulfide gas is 1~10000 mL / min, and the introduction time of the hydrogen sulfide gas is 0.01~100 h.
18. The preparation method according to any one of claims 1 to 4, characterized in that, In step S2, the lithium sulfide solution needs to be stirred before the heat treatment.
19. The preparation method according to claim 18, characterized in that... The stirring speed is 200~1000 rpm, and the stirring time is 0.5~72 h.
20. A solid electrolyte, characterized in that, The solid electrolyte is obtained by the method for preparing the solid electrolyte according to any one of claims 1 to 19.
21. A lithium-ion battery, characterized in that, The lithium-ion battery includes the solid electrolyte of claim 20, or the solid electrolyte obtained by the preparation method of any one of claims 1 to 19.
Citation Information
Patent Citations
Sulfide solid-state electrolyte, preparation method thereof, solid-state electrolyte sheet and solid-state battery
CN113839086A
Preparation method of sulfide electrolyte
CN115101807A
Method for liquid-phase preparation of doped argyrodite type sulfide solid electrolyte with high ionic conductivity
CN114725511A
KR20230084686A